2018
DOI: 10.1186/s12913-018-2931-2
|View full text |Cite
|
Sign up to set email alerts
|

Health services in Trinidad: throughput, throughput challenges, and the impact of a throughput intervention on overcrowding in a public health institution

Abstract: BackgroundThroughput might be partially responsible for sub-optimum organisational and medical outcomes. The present study examined throughput and the challenges to ensuring optimum throughput in hospitals, and determined the effectiveness of a throughput intervention in reducing overcrowding in a public healthcare institution in Trinidad and Tobago.MethodsFirst, a literature review of throughput and its processes in relation to improving hospital care was conducted. Second, the challenges to throughput in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Our findings are relevant to broader health systems strengthening in T&T, because many proposed enablers of drug access would enhance overall health system performance. For instance, recent reports have suggested that institutional process inefficiencies, such as delays in hospital diagnostics resulting from inadequate staffing, create significant barriers to accessing health services in T&T. 24,25 Themes for policy reform from our study, such as increased standardization of intra-and interinstitutional processes in the pharmaceutical sector, may therefore be relevant in addressing other health system inequities as well, including access to diagnostic services and wait times for specialist care. 25 An underlying objective of our study was to develop health system capacity in T&T by equipping local stakeholders with policy-relevant data.…”
Section: Discussionmentioning
confidence: 89%
“…Our findings are relevant to broader health systems strengthening in T&T, because many proposed enablers of drug access would enhance overall health system performance. For instance, recent reports have suggested that institutional process inefficiencies, such as delays in hospital diagnostics resulting from inadequate staffing, create significant barriers to accessing health services in T&T. 24,25 Themes for policy reform from our study, such as increased standardization of intra-and interinstitutional processes in the pharmaceutical sector, may therefore be relevant in addressing other health system inequities as well, including access to diagnostic services and wait times for specialist care. 25 An underlying objective of our study was to develop health system capacity in T&T by equipping local stakeholders with policy-relevant data.…”
Section: Discussionmentioning
confidence: 89%
“…With the high economic burden of non-communicable diseases (NCDs), appropriate funding of the health sector in this small island developing state is a major step towards tending to the needs of the population. Public health services are currently free for patients, however, there has been a multitude of reports highlighting the poor performance of the public health sector in large part due to overcrowding [8,9]. This has been attributed to poor hospital throughput -defined as the number of patients served in a unit of time [8].…”
Section: Discussionmentioning
confidence: 99%
“…Public health services are currently free for patients, however, there has been a multitude of reports highlighting the poor performance of the public health sector in large part due to overcrowding [8,9]. This has been attributed to poor hospital throughput -defined as the number of patients served in a unit of time [8]. With the increased demand for hospital beds and high volume of angiograms and PCIs, hospitals remain under constant pressure to provide patients with appropriate post-procedural care and safe discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Bahall [9] suggests that over the last few decades Trinidad and Tobago's health services have been plagued by inefficiencies partly emanating from poor throughput processes. He argues that reports from numerous commissions, hospital administrators, and healthcare providers have alluded to inefficiencies and poor throughput processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He argues that reports from numerous commissions, hospital administrators, and healthcare providers have alluded to inefficiencies and poor throughput processes. Furthermore, Bahall [9] states that in 1970, the editorial of a daily newspaper reported that a full-scale enquiry into the concern was needed, since the crisis in the nation's health services seems to be getting dangerously close to the point of total collapse, (Bahall [9]).…”
Section: Literature Reviewmentioning
confidence: 99%